Ioannis K. Hassiotis, Ο Οδυσσέας στις θάλασσες του νότου: Η ελληνική παρουσία στις υπερπόντιες κτήσεις της Ισπανίας (16ος–17ος αι.), [Odysseus in the south seas: The Greek presence in the overseas dominions of Spain (16th–17th century] - Birtachas, Stathis (The Historical Review/La Revue Historique, 2025)
Review of Ioannis K. Hassiotis, Ο Οδυσσέας στις θάλασσες του νότου: Η ελληνική παρουσία στις υπερπόντιες κτήσεις της Ισπανίας (16ος–17ος αι.), [Odysseus in the south seas: The Greek presence in the overseas dominions of Spain (16th–17th century]